c-Jun N-terminal Kinase Contributes to Norepinephrine-Induced Contraction Through Phosphorylation of Caldesmon in Rat Aortic Smooth Muscle - Youn Ri Lee; Chang-Kwon Lee; Hyo-Jun Park; Hyojin Kim; Junghwan Kim; Jaeheung Kim; Keun Sang Lee; Yun Lyul Lee; Kyung Ok Min; Bokyung Kim (Elsevier, 2006)
Abstract.: Vascular smooth muscle contraction is mediated by activation of extracellular signal-regulated kinase (ERK) 1/2, an isoform of mitogen-activated protein kinase (MAPK). However, the role of stress-activated protein kinase/c-Jun N-terminal kinase (JNK) in vascular smooth muscle contraction has not been defined. We investigated the role of JNK in the contractile response to norepinephrine (NE) in rat aortic smooth muscle. NE evoked contraction in a dose-dependent manner, and this effect was inhibited by the JNK inhibitor SP600125. NE increased the phosphorylation of JNK, which was greater in aortic smooth muscle from hypertensive rats than from normotensive rats. NE-induced JNK phosphorylation was significantly inhibited by SP600125 and the conventional-type PKC (cPKC) inhibitor Gö6976, but not by the Rho kinase inhibitor Y27632 or the phosphatidylinositol 3-kinase inhibitor LY294002. Thymeleatoxin, a selective activator of cPKC, increased JNK phosphorylation, which was inhibited by Gö6976. SP600125 attenuated the phosphorylation of caldesmon, an actin-binding protein whose phosphorylation is increased by NE. These results show that JNK contributes to NE-mediated contraction through phosphorylation of caldesmon in rat aortic smooth muscle, and that this effect is regulated by the PKC pathway, especially cPKC. Keywords:: c-Jun N-terminal kinase, mitogen-activated protein kinase, vascular smooth muscle contraction, caldesmon, hypertension